IMPLEMENTATION OF PRODUCT DIFFERENTIATION LEARNING CNC SUBJECT FOR XI TPM 2 STUDENTS AT SMKN 1 SINGOSARI - Nur Roziqin, M Akhsanu; Muhammad Rilo Pambudi; Aris Ansori; Siti Faizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Current CNC technology is continually evolving, which necessitates ongoing innovation in classroom teaching for vocational high school students to achieve effective and efficient understanding. So far, the methods commonly used for CNC subjects still rely on conventional methods, such as memorization and group practice. Therefore, as a teacher, it is important to integrate practical and theoretical understanding in teaching by selecting the appropriate teaching methods. Besides choosing the right teaching methods, a teacher must also be able to reflect on the learning outcomes for continuous evaluation, one way being through classroom action research (CAR). In this CAR, the researcher will use various job sheets provided to students to enhance their understanding and practical skills in operating CNC machines. The researcher presents findings using a descriptive quantitative method as it relates to the actual conditions observed in the classroom. The subjects of this study are 36 students from class XI TPM 2, and the process will be divided into three cycles to measure the students' mastery index. Based on the research results, with the implementation of different job sheet models given to the students, the mastery index was 75% in cycle 1, 80.5% in cycle 2, and 88.8% in cycle 3. The increasing mastery index indicates that the evaluation of job sheet provision by the teacher was successful. This improvement in the mastery index is expected to be accompanied by an increase in student engagement in the classroom and teacher activity.